Components of visual illusion - MARTIŠIUS, V. (Psichologija, 1997)
In the present article, based on the works of various authors, a conclusion is made that most visual illusions are caused by several mechanisms acting jointly. Special attention is given to Hoffman’s ideas, showing how the Lie transformation group model could be applied to explain angle illusions. The modificed Hoffman’s rule is as follows. ldentify the first infinitesimal operator generating the orbits corresponding to the distorted part of a figure. Identify the second infinitesimal operator generating the orbits along which the structure of the surrounding context is the simplest. Form a linear combination of these two operators, weighing the first operator mare strongly. This linear combination of infinitesmal operators will generate the illusion. The rule is a convenient mathematical instrument to describe the averaging (assimilation’s) processes in producing angle illusions. The shortcomings of the rule are also discussed.